The Relationship of Executive Functions and Speech Production in Senior Preschool Children: Working Memory and Storytelling - Veraksa, A.N.; Oshchepkova, E.S.; Bukhalenkova, D.A.; Kartushina, N.A. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2019)
The article presents the data of the study of working memory and features of oral monologue speech in preschool children. 269 children (133 boys and 136 girls) aged 5-6 years (M=5.6 years; Sd=0.48) attending the senior group of kindergarten in Moscow were examined. Features of oral monologue speech development were studied using methods developed in the Russian neuropsychology: tasks for retelling the text and compiling the story of a series of pictures. General neuropsychological parameters, separate lexical and grammatical (morphology and syntax) indicators, macrostructure of the narrative were analyzed in the evaluation of children's responses. As a result of the correlation and cluster analysis, similar links were obtained: the level of working memory development in preschoolers is correlated with such indicators of the child's speech development as semantic completeness of the text, its adequacy, programming of speech message, the number of words and sentences in the text, the development of macrostructure and the type of narrative. Based on the results, it is concluded that the most general and global indicators of the macrostructure of the text are significantly associated with the development of working memory. At the same time, the development of verbal working memory is more associated with the development of speech in preschool children compared to visual working memory. The authors come to the conclusion that with a well-developed auditory working memory, the child's speech will be more correct lexically and grammatically. В статье приводятся данные исследования рабочей памяти и особенностей устной монологической речи у детей старшего дошкольного возраста. Было обследовано 269 детей (из них 133 мальчика и 136 девочек) в возрасте 5-6 лет (М=5,6 лет; SD=0,48), посещающих старшую группу детского сада в г. Москве. Особенности развития устной монологической речи изучалась с помощью методов, разработанных в отечественной нейропсихологии: заданий на пересказ текста и составления рассказа по серии картинок. При оценке ответов детей анализировались общие нейропсихологические параметры, отдельно лексические и грамматические (морфология и синтаксис) показатели, а также структура нарратива. В результате корреляционного и кластерного анализа были получены схожие результаты: с уровнем развития рабочей памяти у детей в дошкольном возрасте наилучшим образом устойчиво коррелируют такие показатели развития речи ребенка, как смысловая полнота нарратива, его адекватность, программирование речевого сообщения, количество слов и предложений в тексте, развитие макроструктуры и тип нарратива. На основании полученных результатов делается вывод о том, что самые общие и глобальные показатели макроструктуры нарратива значимо связаны с развитием рабочей памяти. При этом развитие слуховой рабочей памяти в большей степени связано с развитием речи у дошкольников по сравнению со зрительной рабочей памятью. Авторы приходят к заключению, что при хорошо развитой слуховой рабочей памяти речь ребенка будет более правильна в лексическом и грамматическом отношениях.